VETERAN-CENTRIC VD-HCBS: HOW VETERANS USE FLEXIBLE SPENDING BUDGETS TO MEET INDEPENDENT LIVING GOALS. (11th November 2018) - Flanagan, S; Anthony, J; Dyson, L; Page, N; Williams, M; Brady, P
Abstract: The Veterans-directed Home and Community-based Services (VD-HCBS) Program provides eligible Veterans at risk of institutional placement the opportunity to receive needed HCBS using a self-directed approach and a flexible spending budget. A 2017 study examined how Veterans enrolled in six VD-HCBS programs located in five VA Regions used flexible spending budgets to purchase needed HCBS during FFY'2016. Budget authorizations, spending plans, monthly spending reports and universal billing forms were collected for 53 Veterans. Additional data was collected through phone interviews with 17 Program partners (VAMCs, ADNAs and FMS entities). Characteristics of Veterans and their workers; the type and amount of HCBS LTSS spending incurred and emergency backup and planned savings funds accumulated and used by Veterans, and the interaction of VAMCs, ADNAs and FMS entities to support Veterans were analyzed. Findings revealed that Veterans hired 1.8 workers, on average, who were predominately female (64.0%), with the majority working part-time and related to the Veteran (66%). Veterans used the majority of their budget funds to directly hire and manage their personal care workers with a minimal amount spent for agency-based services. Use of approved goods and services was minimal in part, due to variation in VAMCs' policies. Average annual administrative fees per Veteran were 18.5% of total program expenses compared to 50% for the VA's Homemaker Home Health Program. Although the majority of programs adhered to procedures for monthly spending reporting and invoicing, variation observed could benefit from standardization and education for VAMCs, ADNAs, FMS entities and VA Claims Processing staff.